The Eastern Partnership – A Premise for an Enhanced EU-Eastern Neighbours Cooperation Relationship - Oana Mocanu (Romanian Journal of European Affairs, 2009)
The enlargement of the European Union towards the Central and Eastern Europe has brought to attention the necessity to reshape the EU institutional framework and specific policies addressing its new neighbourhood. Repeatedly stating that the European Neighbourhood Policy (ENP) is not a preceding phase for membership, the European Union also embraced the Polish-Swedish initiative for an Eastern Partnership (EaP). Meant at first to counterbalance the Union for Mediterranean project, the EaP has developed into a distinct project, with specific and ambitious cooperation goals, a positive and constructive agenda meant to support six countries (Ukraine, Moldova, Georgia, Azerbaijan, Armenia and Belarus) develop and harmonize with the European standards and, at the same, attempting to build and further develop an Eastern dimension of the ENP. The questions of the efficiency of the conditionality derived from the EaP and also the complementarity of this initiative with other regional projects in the area can also be important matters of concern.